The role of workforce diversity in shaping employee inclusion in organizations - Karsudjono, Anthonius; Kadir, Abdul; Ritawaty, Noor; Fatih, Hardika Muhammad; Audah, Ali (Annals of Human Resource Management Research, 2025)
Purpose: This study investigates how Generational Diversity (GD), Gender Diversity (GE), Disability Orientation (DO), Socioeconomic Status (SES), and Cultural Values (CV) influence Employee Inclusion (EI) in medium- and large-scale organizations in Indonesia. Research Methodology: A quantitative, causal-explanatory design was applied using survey data from 150 employees collected via structured questionnaires on a 5-point Likert scale. Data were analyzed using PLS-SEM with bootstrapping (1,000 resamples) to assess measurement reliability/validity and test structural relationships. Results: Findings indicate that all five diversity-orientation constructs positively and significantly affect Employee Inclusion. Cultural Values and Generational Diversity show the strongest effects, while Gender Diversity, Disability Orientation, and Socioeconomic Status also contribute meaningfully. The model explains about 66% of the variance in EI (R² ? 0.661), and all paths meet significance criteria (t > 1.96; p < 0.05). Conclusions: Employee inclusion is strengthened when organizations intentionally cultivate culturally respectful environments, encourage intergenerational collaboration, ensure gender equity, support employees with disabilities, and reduce SES-based barriers through fair HR practices. Limitations: The study is cross-sectional, context-specific, and relies on self-reported data, which may limit causal inference and generalizability. Contribution: This research integrates multiple diversity dimensions into a single predictive framework, offering evidence-based priorities for leaders and policymakers to design targeted inclusion strategies that enhance engagement and organizational effectiveness.